Dominance of Epsilonproteobacteria associated with a whale fall at a 4204 m depth – South Atlantic Ocean. (December 2017) - Cavalett, Angélica; Silva, Marcus Adonai Castro da; Toyofuku, Takashi; Mendes, Rodrigo; Taketani, Rodrigo Gouvêa; Pedrini, Jéssica; Freitas, Robert Cardoso de; Sumida, Paulo Yukio Gomes; Yamanaka, Toshiro; Nagano, Yuriko; Pellizari, Vivian Helena; Perez, José Angel Alvarez; et al.
Abstract: The deep ocean is the largest marine environment on Earth and is home to a large reservoir of biodiversity. Within the deep ocean, large organic falls attract a suite of metazoans and microorganisms, which form an important community that, in part, relies on reduced chemical compounds. Here, we describe a deep-sea (4204 m) microbial community associated with sediments collected underneath a whale fall skeleton in the South Atlantic Ocean. Metagenomic analysis of 1 Gb of Illumina HiSeq. 2000 reads, including taxonomic and functional genes, was performed by using the MG-RAST pipeline, SEED, COG and the KEGG database. The results showed that Proteobacteria (79%) was the main phylum represented. The most dominant bacterial class in this phylum was Epsilonproteobacteria (69%), and Sulfurovum sp. NBC37-1 (97%) was the dominant species. Different species of Epsilonproteobacteria have been described in marine and terrestrial environments as important organisms for nutrient cycling. Functional analysis revealed key genes for nitrogen and sulfur cycles, including protein sequences for Sox system (sulfur oxidation) enzymes. These enzymes were mainly those of the Epsilonproteobacteria, indicating their importance for nitrogen and sulfur cycles and the balance of nutrients in this environment.